ANALISIS PENGGUNAAN VIDEO GAME ONLINE SEBAGAI MEDIA DAKWAH - Nanda Khairiyah (An-Nufus, 2020)
This article examines the use of online game applications for Islamic da'wah. The purpose of this research is to reveal how much the benefits and effects of online games which are currently favored by netizens for Islamic education. This is with the assumption that the image of online games is not completely negative, as is generally considered by the public. Whereas in online games, as with other information technology products, there are two sides of a coin; negative and positive aspects depending on the users. In the context of Islamic preaching, online games can be used as an effective da'wah medium, given the increasing number of users every day. The research method in uncovering this phenomenon uses qualitative methods. Data analysis based on literature review from various media. Some of the findings that the researcher obtained include: da'wah can take advantage of online games, as well as a number of Islamic online games popping up that are of interest to netizens.